Islamic process in kazakhstan: foreign influence - Aktaulova, B. Zh. (Journal of Oriental Studies, 2016)
The article explores functions of foreign Muslim organizations and charity funds as one of the external factors which impacts on the Islamic process in Kazakhstan.